Exploring Social Media's Power in Enhancing Brand Continuance Intention: Cosmetic Industry - NGUYEN THI PHUONG, Giang; NGUYEN BINH PHUONG, Duy; THAI DONG, Tan (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025, 2025)
This study aims to examine the impact of social media marketing (SMM) strategies on the intention to continue using cosmetics in Ho Chi Minh City. The research framework is grounded in social media marketing theory, focusing on its relationship with customer experience (CUE) and continuance intention (CI). The study also explores the mediating roles of brand awareness (BAW), attitude toward the brand (ATB), and product satisfaction (SAT). Data was collected through an online Google Forms survey, with 516 respondents who are cosmetics users. The analysis was conducted using the partial least squares structural equation modeling (PLS-SEM) approach. The findings reveal that all independent variables - SMM, BAW, ATB, SAT, and CUE - significantly influence continuance intention. Among these, product satisfaction (SAT) has the strongest impact, followed by brand awareness (BAW), attitude toward the brand (ATB), social media marketing (SMM), and customer experience (CUE), respectively. The results highlight the crucial role of enhancing product quality to ensure customer satisfaction, which is fundamental for driving continuance intentions. In addition, leveraging social media marketing to strengthen brand management, foster positive brand attitudes, and improve brand awareness also plays a significant role in encouraging consumer loyalty. This study contributes to the growing body of literature on social media marketing by providing a context-specific evaluation of its impact on continuance intention within Vietnam’s cosmetics industry. However, the study is geographically limited to Ho Chi Minh City, which may affect the generalizability of the findings to other regions. Future research could broaden the scope to include different cities, industries, or consumer demographics. The findings offer actionable insights for cosmetics businesses to optimize social media marketing strategies, enhance product quality, and improve customer satisfaction to foster brand loyalty and continuance intention. The study emphasizes the role of social media in shaping consumer behavior, which can further influence sustainable business practices and consumer engagement in the digital era.